THE TEACHER’S POSITION IN THE CLASSROOM, THEIR ABILITY TO CREATE A POSITIVE ATMOSPHERE, AND THE ORGANIZATION AND REGULATION OF STUDENTS’ DISCIPLINED BEHAVIOR IN CLASS - Umurzakova Dilfuza Ilxomovna; Qarshiyeva Aziza (Bright Mind Publishing, 2026)
This article discusses Jan Amos Comenius’s work “The Great Didactic”, which emphasizes that education is created for every individual and that teaching and upbringing should be carried out in harmony. The work contains a separate chapter dedicated to school discipline. It mainly highlights the high importance of order and discipline and explains the formation of students’ appropriate behavior.
Keywords: School discipline, immorality, knowledge, kindness, education and upbringing.